A qualitative evaluation of a whole-school approach to improving resilience in childhood and adolescence - Zak, Iwona K.; Rubens, Isabella; Abbott, Nicola; McGowan, Jennifer (Frontiers in Education, 2025)
BackgroundWorldwide, 10–20% of youth suffer from mental health problems. Research shows that high levels of resilience may increase resistance against mental and physical distress. In this, a ‘whole-school’ resilience intervention (Anchor Approach) can support children and adolescents. The aim of this study was to understand the intervention effects according to staff, parents and mental health services. Perceptions are explored through intervention sustainability, acceptability, efficacy, feasibility and flexibility and adaptability.MethodsSeven qualitative focus groups were conducted in six schools adopting the Anchor Approach intervention, with participants consisting of parents (N = 4), school staff (N = 12), and Child and Adolescent Mental Health Services (CAMHS; N = 4). Thematic analysis was conducted on the data by two researchers.ResultsFour themes were revealed: (1) “Timeliness,” (2) “Behavioural Impact of the Anchor Approach,” (3) “Engagement with the Anchor Approach,” (4) “Working together.” Participants felt the intervention was timely and changes toward emotion-focused care were found. Variations between schools in its usage resulted in differences in confidence, behavioral changes and care continuity. Dependent on environmental factors, concerns about feasibility were raised regarding implementation, resources and communication of support offered.ConclusionThe Anchor Approach was well utilized and accepted, positively impacting staff confidence, student behavior and staff-student interactions. High levels of acceptability and utilization (with variations) were identified across participants. Staff time and complexity of resources provided may impact intervention feasibility and sustainability.